Persistent organic pollutant levels in eggs of leatherback turtles (Dermochelys coriacea) point to a decrease in hatching success. (March 2016) - De Andrés, Eva; Gómara, Belén; González-Paredes, Daniel; Ruiz-Martín, José; Marco, Adolfo
Abstract: Sea turtles are susceptible to environmental pollution, since many harmful effects have been reported for different chemicals over the last two decades. In this context, persistent organic pollutants (POPs), such as polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) are of particular concern due to their endocrine-disrupting nature. The aims of this study were to provide additional baseline data on PCB and PBDE concentrations in eggs of Dermochelys coriacea; and to investigate whether any of the congeners could compromise reproductive success in this species. A total of 18 nests from different females were studied during the nesting season of 2008 at Reserva Pacuare Beach, in the Caribbean side of Costa Rica. Reproductive parameters (viability, fertility and hatching rates) were calculated for all nests and hatchling morphometrics were successfully measured in 8 of them. Two to three fresh eggs per nest were taken for contaminant study. Different congeners of POPs were purified and identified using gas chromatography (GC) coupled to an ion trap detector (GC-ITD MS/MS), as described below. Mean ± SD concentrations were calculated for POP congeners within each nest and clustering was also evaluated. Correlations were performed searching for potential relationships with reproductive parameters. POP levels were similar to those reported in French-Guiana populations and slightly lower than those associated to Florida populations. Sum of PBDEs showed a negative correlation to the hatching success, suggesting potential harmful effects of these contaminants on the reproduction of leatherbacks. Highlights: We quantify POP congeners in eggs of leatherback turtles. We search for correlations between POP concentrations and reproductive parameters. Sum of PBDEs was significantly and negatively correlated to hatching success. Knowledge in this field could lead into a better management for this species.